Study of feto-maternal outcome in twin pregnancy - Sheth, Kenan; Sheikh, Amira M.; Shah, Margi A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In modern obstetrics with advanced ultrasonographic techniques and color Doppler, multiple pregnancy and associated condition like chorionicity, growth discordance, vascular complications, twin to twin transfusion syndrome, intrauterine death of one or more fetus and congenital anomalies can now be diagnosed at early stage of gestation. Vigilant obstetric care during antepartum, intrapartum and postpartum period decreases maternal morbidity and mortality as well as improves fetal outcome in twin pregnancy. Methods: This is a randomized prospective study of 250 patients of multiple pregnancy admitted at our institute from July 2020 to June 2022 including all emergency as well as registered patients. In all cases a detailed history was taken and all routine investigations were done. All information was entered in a proforma and the fetomaternal outcome of twin pregnancy was analysed. Results: Around 67% patients had onset of labor after 32 weeks of gestation, rest 32% patients had onset of labor at or before 32 weeks of gestation. The 55% patients underwent lower segment caesarean section and 45% patients delivered vaginally. We observed highest incidence of twins in age group 21-30 years. Maximum number of patients 59% were multigravida compared to primigravida. Conclusions: Multiple pregnancy is considered as “high risk pregnancy”. hence early diagnosis of multiple pregnancy is essential in reducing maternal and perinatal morbidity and mortality.